The impact of host development and density stress on the diversity of microbial communities in the gut and its surrounding environment of the Chinese alligator - Chong Wang; Changcheng Li; Peng Liu; Song Zhang; Yongkang Zhou; Xuesong Zhang; Yingchao Wang; Ruoya Liu; Xiaobing Wu; Haitao Nie (Ecology and Evolution, 2024)
Abstract The Chinese alligator (Alligator sinensis) is currently an endangered species due to a combination of factors, including climate change, anthropogenic activities, and habitat fragmentation. Captivity plays a crucial role in mitigating the decline of the Chinese alligator population. Currently, there is a lack of clarity regarding the influence of host development and captive conditions on the gut microbiota of Chinese alligators. The aim of the study was to investigate the gut bacterial communities of Chinese alligators and their surrounding environmental bacterial communities using 16S rRNA sequencing. The primary gut flora of Chinese alligators consists of Proteobacteria, Bacteroidetes, and Firmicutes. Proteobacteria is the most abundant and efficient settler in the gut, water, and sediment. PCoA and Adonis test revealed significant differences in bacterial communities across these habitats. Venn analysis revealed overlap in OTUs among the gut, water, and sediment, varying with growth stage and density stress. Different growth stages of Chinese alligator guts harbor distinct pathogenic bacteria, requiring attention. Density stress leads to an increase in pathogenic bacteria, a decrease in gut absorption efficiency. PICRUst2 predicts more abundant metabolic pathways related to gut function during high‐density stress, possibly linked to Roseburia. SourceTracker Analysis indicated that water bacteria have a greater impact on Chinese alligator gut bacteria than sediment, and density stress significantly affects the contribution of environmental microorganisms to the gut microbes of Chinese alligator. BugBase analysis identified water body microbes as the main source of “potentially pathogenic” phenotypes in the gut microbiota. RDA analysis found dissolved oxygen (DO) in water to be the most significant factor influencing water microorganisms, positively correlated with certain pathogenic strains. These findings enhance our understanding of the significance of microbial communities in the gut and surrounding aquatic environment of the Chinese alligator. Furthermore, they provide theoretical support for environmental regulation, disease control, and healthy breeding.